Potential Analysis of a Hybrid Sun-Wind-Battery Power Generation for Stand Alone Street Lighting on the Merah-Putih Bridge Ambon - Eka Adhitya Dharmawan; Eka Rahmat Mahayani Anthonio Putera Lilipaly; Noce Novi Tetelepta (International Journal Multidisciplinary Science, 2026)
This study investigates the feasibility of a hybrid renewable energy system consisting of solar photovoltaic, wind turbine, and battery storage to supply individual street lighting on the Merah Putih Bridge, Ambon. Renewable resource assessment was conducted using measured wind data and NASA solar radiation data for the period 2018–2020. The results indicate that the study location possesses favorable renewable energy potential, with an average wind speed of approximately 5.57 m/s and solar radiation exceeding 4 kWh/m²/day throughout the year. Seasonal analysis demonstrates complementary behavior between solar and wind resources, supporting the suitability of hybrid energy implementation. The hybrid system was designed to supply a 60 W LED lamp operating for 12 hours per day, corresponding to a daily energy demand of 720 Wh. The proposed configuration includes a 200 W photovoltaic module, a 400 W wind turbine, and a 12 V 100 Ah battery. Performance analysis shows that the system can generate approximately 3150 Wh/day, ensuring reliable operation with sufficient energy reserve and more than one day of battery autonomy. Economic evaluation indicates a total investment cost of approximately 1350 USD, with a Levelized Cost of Energy of 0.13 USD/kWh and a payback period of 13.7 years under a local electricity tariff of 0.086 USD/kWh. Lifecycle cost comparison demonstrates that the hybrid system is competitive with grid extension alternatives, particularly when infrastructure costs are considered. Additionally, the system can reduce approximately 0.98 tons of CO₂ emissions annually per lighting unit. The results confirm that the proposed hybrid solar–wind–battery system is technically feasible, environmentally sustainable, and suitable for decentralized bridge lighting applications.